PELAKSANAAN PROGRAM KEWIRAUSAHAAN PADA PUSAT KEGIATAN BELAJAR MASYARAKAT DI KAB. SLEMAN - Pranoto, Aji (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2013)
Unemployment and poverty in Yogyakarta, especially in the districts of Sleman both rural and urban is still high. Efforts have been taken by the government with the entrepreneurship education programs (PKM). The program is the Course Rural Entre-preneurial (KWD) and Course Entrepreneurial City (KWK). The purpose of the research is to figure out the implementation of administration, process, achievement of results, follow-up mentoring business, and the factors supporting and inhibiting the implementation of the program (KWD) and (KWK) at the Community Learning Center (PKBM) in Sleman. Data are collected by questionnaires, interviews and documentation. The data obtained are then analyzed using descriptive method. Results show that the average value of implementation of the program administration KWD & KWK, implementation process, and follow-up mentoring are 2.331, 2.406, and 2.338 respectively, hence categorized enough. Meanwhile, an achievement of objectives in average of 2,176 and categorized is less. Supporting factors are the aspect of understanding, ability and experience in conducting, has the electronic media (computer) 70% and a good enough office space, as well as funding (block grants) from the government. Limiting factors are the reliance on a particular board member; un-expert tutor, low motivation learners, and nonproductive citizens. Furthermore, the limititions are (PKBM) which insufficient Internet connection and guide books, lack of funds to open a business stimulant, tutor small honorarium, and the difficulty of finding an external funding sources.